Injury study of the 6-year-old pediatric thorax and abdomen in frontal sled tests using different computational models - Li, Haiyan; Lv, Wenle; Hynčík, Luděk; Zhou, Bingbing; Zhao, Hongqian; Cui, Shihai; He, Lijuan; Ruan, Shijie (Frontiers in Future Transportation, 2022)
The correct use of a child restraint system (CRS) is an effective internationally recognized measure to protect the safety of child occupants which can reduce the probability of child road traffic accident deaths by 54–80%. Finite element (FE) analysis is one important method with which to study the protection of child occupants. The aim of this study was to investigate thoracic and abdominal injuries and the protective effect of CRS on child occupants in 6-year-old (6YO) children in a frontal sled test using different computational models. In this study, a verified FE model of a 6YO child occupant was placed in the FE model of a CRS with a three-point safety belt. In the simulation setup phase, the frontal sled simulation of the 6YO FE model was reconstructed by applying the AAMA pulse. Based on the simulation data of the Q6 dummy FE model (Q6) and the 6YO child Virthuman model (V6) from previous studies, the frontal sled test simulation of a verified 6YO child FE model with detailed anatomical structures (TUST IBMs 6YO) was carried out to analyze pediatric thorax and abdomen injuries under the same experimental conditions. According to the simulation results, the variation tendencies of the simulation responses such as chest acceleration and compression are consistent with each other, which can provide effective information for the design of a CRS. In addition, the simulation results of the TUST IBMs 6YO can provide a variety of simulation data, such as the maximum first principal strain value and nephogram, of the internal organs of the chest and abdomen, providing a theoretical basis for the performance analysis and later development of a CRS.